2014
DOI: 10.1124/dmd.114.058511
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Liver Cirrhosis on the Pregnane X Receptor–Mediated Induction of CYP3A1 and 3A2 in the Rat

Abstract: Conflicting results have been obtained by clinical studies investigating the effect of liver cirrhosis on enzyme induction. Because ethical concerns do not give consent for methodologically rigorous studies in humans, we addressed this question by examining the effect of the prototypical inducer dexamethasone (DEX) on the pregnane X receptor (PXR)-mediated induction of CYP3A1 and 3A2 in a validated animal model of liver cirrhosis obtained by exposure of rats to carbon tetrachloride. For this purpose, we assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…For further evaluation of the role of CYP3A–UGT1A interactions, we focused on dexamethasone, a strong inducer of hepatic CYP3A1, CYP3A2, UGT1A1, and 1A6 in rat (De Martin et al, ; Ghosal, Sadrieh, Reik, Levin, & Thomas, ; Jemnitz, Veres, Monostory, & Vereczkey, ). The UGT‐mediated suppression of CYP3As should be affected if dexamethasone treatment induces CYP3As and UGT1As to different extents.…”
Section: Resultsmentioning
confidence: 99%
“…For further evaluation of the role of CYP3A–UGT1A interactions, we focused on dexamethasone, a strong inducer of hepatic CYP3A1, CYP3A2, UGT1A1, and 1A6 in rat (De Martin et al, ; Ghosal, Sadrieh, Reik, Levin, & Thomas, ; Jemnitz, Veres, Monostory, & Vereczkey, ). The UGT‐mediated suppression of CYP3As should be affected if dexamethasone treatment induces CYP3As and UGT1As to different extents.…”
Section: Resultsmentioning
confidence: 99%
“…Ten male Wistar rats, aged 5 weeks (body weight 150-170 g), were obtained from Charles River Italia (Calco, Lecco, Italy). They were kept under controlled environmental conditions and fed with standard diet for 2 weeks before the beginning of the treatment [31]. Then, the animals were randomized into two experimental groups, both fed with high-fat diet (HFD = kcal from 23.5% protein, 18.4% carbohydrate, and 60.3% fat; Altromin; Lage, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For example, microRNAs are the major determinants of gene expression at the post-transcriptional level, suppressing gene expression by mRNA cleavage or translational inhibition. 53 , 54 Moreover, it has been reported that the expression of rat hepatic Cyp3a2 is predisposed to regulation by nuclear transcription factors or nuclear receptors, 55 57 which may also be involved in the regulatory effect of XKB on expression of rat Cyp3a2.…”
Section: Discussionmentioning
confidence: 99%